Clinical Frailty Scale - frailty assessment and rehabilitation potential - Szymon Wiśniewski; Weronika Hołownia; Wiktoria Julia Krzesłowska; Paulina Pytel; Kamila Szewczyk; Bartłomiej Szewczyk (Kazimierz Wielki University, 2024)
Background: Studies show a significant increase in frailty prevalence among older adults worldwide. Fortunately, several well-established and user-friendly screening tools can effectively identify frailty in older adults. Objectives: This article examines the Clinical Frailty Scale's effectiveness in informing treatment decisions for older adults in ambulatory care settings, analyzing its potential to improve patient care. Methods: On April 1, 2024, the PubMed database was searched for articles on the Clinical Frailty Scale in elderly patients. The 116 most pertinent and current articles, written in English and published within the past few years, were analyzed, and 38 were selected and categorized by content and topic.   Limitations: This study is limited because it is not a meta-analysis and thus does not examine the quality of the evidence presented in each article. Conclusions: Frailty research has illuminated aging and its potential biological causes. The Clinical Frailty Scale effectively identifies vulnerable individuals. By using the CFS to assess frailty risk, healthcare providers can personalize treatment plans and improve overall care for older adults.